The effects of naltrexone on retention in treatment and being opioid-free in opioid-dependent people: A systematic review and meta-analysis - Zangiabadian, Moein; Golmohammadi, Saeid; Nejadghaderi, Seyed Aria; Zahmatkesh, Mohammad Mahdi; Nasiri, Mohammad Javad; Sadeghian, Majid (Frontiers in Psychiatry, 2022)
Background: Opioid dependency is a chronic relapsing disorder for which different therapeutically interventions have been developed. Naltrexone is a non-selective opioid antagonist that can be utilized for maintenance therapy in opioid dependency. In this systematic review, we aimed to evaluate the effects of naltrexone on retention in treatment and being opioid-free. Methods: We systematically searched PubMed and EMBASE databases up to February 5, 2022, using the following keywords: “Naltrexone”, “Substance abuse”, “Drug abuse”, “Opiate-related disorder”, and “Opioid dependence”. Studies that included opiate-dependent individuals who were treated with naltrexone and assessed retention in treatment or being opioid-free were included. Two authors independently used the Cochrane risk-of-bias tool for quality assessment. A random effect model in Comprehensive Meta-Analysis software was used for the conduction of the meta-analysis. We performed subgroup analysis to evaluate the effects of naltrexone types on outcomes. Results: Eighteen studies, including 2280 participants met our inclusion criteria. The duration of treatment ranged from 21 days to 24 months. The retention in treatment with naltrexone was 63% higher than controls (odds ratio (OR): 1.64 (95% confidence interval (CI), 0.78-3.44). The OR for being opioid-free was 1.63 (95% CI, 0.57-4.72). Injectable naltrexone was significantly effective on retention in treatment (OR 1.86; 95% CI, 1.17-2.98). Conclusions: We found that naltrexone could be useful for retention in treatment and being opioid-free, however, the findings were not significant. Further high-quality and large-scale observational studies are recommended.